Rasch Analysis of Authentic Evaluation of Young Children's Functioning in Classroom Routines - Morales-Murillo, Catalina Patricia; García-Grau, Pau; McWilliam, R. A.; Grau Sevilla, Ma Dolores (Frontiers in Psychology, 2021)
This study evaluated the functioning of children in early childhood education classroom routines, using the 3M Functioning in Preschool Routines Scale. A total of 366 children aged 36 to 70 months and 22 teachers from six early childhood education centers in Spain participated in the study. The authors used the Rasch model to determine the item fit and the difficulty of the items in relation to children’s ability levels in this age range. The Rasch Differential Item Functioning (DIF) analysis by child age groups showed that the item difficulty differed according to the children’s age and according to their levels of competence. The results of this study supported the reliability and validity of the 3M scale for assessing children’s functioning in preschool classroom routines. A few items, however, were identified as needing to be reworded and more difficult items needed to be added to increase the scale difficulty level to match the performance of children with higher ability levels. The authors introduced the new and reworded items based on the results of this study and the corresponding ICF codes per item. Moreover, the authors indicate how to use the ICF Performance Qualifiers in relation to the 3M scale response categories for developing a functioning profile for the child.